2019
DOI: 10.2147/prbm.s228902
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Bright Side of Stressed Frontline Employees in Service Recovery: The Combination Causes of Organizational Empowerment and Self-Regulation Processes</p>

Abstract: PurposeThis study aims to extend the previous research on the structural relationships between organisational empowerment and frontline employees’ behaviours by exploring the role of the self-regulating processes and its impact on service recovery performance (SRP).MethodsThis study adopts fuzzy-set qualitative comparative analysis (fsQCA). Following the procedure of applying fsQCA, including data calibration, truth table construction and fsQCA analysis, the 287 dyadic data from the express mail industry was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Future research is needed to examine how various combinations of contextual factors impact the stressor–strain relationships demonstrated here. Aside from structural equation modeling analysis, fuzzy-set-qualitative comparative analysis may provide such insights into complex and possibly contradicting cases (Woodside, 2013 ; Yueh, Lu, & Lin, 2016 ; Zhang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research is needed to examine how various combinations of contextual factors impact the stressor–strain relationships demonstrated here. Aside from structural equation modeling analysis, fuzzy-set-qualitative comparative analysis may provide such insights into complex and possibly contradicting cases (Woodside, 2013 ; Yueh, Lu, & Lin, 2016 ; Zhang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large stream of previous psychological research has shown that the crowdsourcing services provided by Sojump are reliable. 63,64 Before the survey, we showed the participants a cover letter that explained the objectives of this research and guaranteed anonymity. Then the participants completed the items the authors presented.…”
Section: Data and Methods Participants And Proceduresmentioning
confidence: 99%
“…The present research is the first to consider FLEs' SRA as a potential job demand for their emotional responses. A combination causes analytical results indicated that the FLEs with high level of SRA perform well in complaint handling, even for the stressed FLEs (Zhang, 2019). Yet, the mechanism of SRA that dual impact on customer post-recovery satisfaction still needs to be explored.…”
Section: Introductionmentioning
confidence: 95%